Project SCOPE: a National Training Initiative to improve capacity of providers to support children impacted by prenatal opioid exposure using the ECHO model™ - Weber, Stephanie; Hardesty, Canyon; Witwer, Andrea; Dahl, Ethan; Bush, Elsie; Thomas, Jessy; Baker, Tai; Dudley, Ally; Moody, Eric J. (Frontiers in Public Health, 2024)
IntroductionNeonatal abstinence syndrome (NAS) is a complex condition resulting from prenatal substance exposure that has become increasingly prevalent as a result of the opioid epidemic. NAS can lead to long-term developmental challenges. Interdisciplinary teams with experience working with children with disabilities that focus on social determinants of health can be effective at supporting families affected by NAS. Unfortunately, interdisciplinary teams often lack sufficient training, ongoing practice support, and public health policies to support these families. The objective of this project was to determine the feasibility and impact of a National Training Initiative, called Project SCOPE, to improve the capacity of providers to address the needs of children with NAS and their families.MethodsFourteen (14) sites were trained to fidelity in the ECHO model and SCOPE curriculum, and then each team implemented this model for at least one, eight to 12 session series between 2019–2022. The reach, impact, satisfaction, and intention to implement the model were assessed from administrative records, pre/post surveys, and post-session evaluations.ResultsSCOPE state teams delivered the curriculum to 9,392 individuals across 33 US states. Surveys from 2,197 individuals were used for analysis. Most participants (84%) had previous training in trauma informed care, but only 53% had any training on the NAS or the opioid crisis' impact on children. Satisfaction with SCOPE sessions was high (96.4%), and there was a statistically significant increase of self-reported knowledge change from pre- to post-SCOPE. Over 94% reported their skills increased because of participation. Over 97% of participants indicated their motivation to work with this population increased from SCOPE participation and that they could successfully apply what they learned. Almost 70% reported they were “very” or “extremely” likely to use their new skills.DiscussionProject SCOPE is a highly effective and impactful model that can radically improve capacity to support children affected by the opioid epidemic, thereby increasing the capacity of our healthcare system to respond to this epidemic. Moreover, this model can be rapidly deployed and reach a wide geographic region, especially areas that are affected by the opioid crisis and underserved rural communities.